Immunological Properties of Friend Virus from Mouse Spleen Obtained by Gel Filtration - Chan, S. P. (1969)
Gel filtration, with Sephadex G-200, was utilized to obtain Friend virus (FV) from infected spleen homogenate. Highly infectious and immunologically active material was eluted as a large initial protein peak, whereas hemoglobin and other noninfectious materials were found in two subsequent peaks. Fractions that made up the first peak were reactive in serological tests with antiserum towards FV. Formalinized fractions from the first peak, when combined with Freund's complete adjuvant, were able to protect mice against subsequent FV challenge. Further purification of antigen was carried out by sucrose gradient ultracentrifugation.